BAHASA SAPAAN DALAM PERTUNJUKAN WAYANG KULIT PURWA GAYA SURAKARTA - Purbo Asmoro (Gelar : Jurnal Seni Budaya, 2010)
This research aims ta finding out the answers to the questions : (1) What are types of greetings  in wayang kulit purwa performance of  Surakarta style? Why are there many kinds of greeting types? and What are the functions and meaning of greetings? The research studying greetings in wayang kulit purwa performance of Surakarta style uses sociolinguistic approach, namely Dell Hymes’ theory of speech components. The factors which determine someone’s utterance are setting or scene (s), participants (p), end (e), act of sequence (a), key (k), instrumentalities (i), norm of interaction (n), and genre (g). The functions of greetings in context are analyzed using cognitive, evaluative, and a affective functions. Function analysis and the context meaning of greetings in wayang kulit purwa performance of Surakarta style encompass cognitive function which analyze the expression of  ideas, concepts, and thought of the dialogue and conversation between wayang figures; evaluative function which ensures, declares, conveys and delivers  attitudes and values contained in the dialogue between the figures; and affective funtion which transfers the emotion and feeling of the figures or participants of a dialogue in the wayang kulit purwa performance. The greetings of wayang kulit figures contain the elements of moral, ethic, social education, and philosophical principles of life. Key words : wayang kulit, performance, greeting